2018
DOI: 10.3892/ol.2018.9395
|View full text |Cite
|
Sign up to set email alerts
|

Emerging function of N6‑methyladenosine in cancer (Review)

Abstract: N6-methyladenosine (m6A) modification in RNA has been implicated in diverse biological processes including the maintenance of embryonic stem cells, early development and diseases. Although the m6A modification was discovered several decades ago, its biological function remained unclear. The recent discovery of enzymes responsible for 'writing' or 'erasing' the modification and single-nucleotide resolution mapping by next-generation sequencing technology have revealed its function in biological processes. Its e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 74 publications
0
36
0
Order By: Relevance
“…The NF-κB signaling pathway is a classic pathway related to inflammation and immune regulation in RA [37]. Growing data showed that expression and regulation of m 6 A methylation-related genes are associated with a variety of immune signaling pathways, particularly the NF-κB pathway [8,18]. In this study, METTL3 has been found to be upregulated in peripheral blood monocytes, the critical cell type in PMBCs involved in inflammation and immune regulations.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The NF-κB signaling pathway is a classic pathway related to inflammation and immune regulation in RA [37]. Growing data showed that expression and regulation of m 6 A methylation-related genes are associated with a variety of immune signaling pathways, particularly the NF-κB pathway [8,18]. In this study, METTL3 has been found to be upregulated in peripheral blood monocytes, the critical cell type in PMBCs involved in inflammation and immune regulations.…”
Section: Discussionmentioning
confidence: 54%
“…During the past few years, the role of N 6 -methyladenosine (m 6 A) methylation of RNA in autoimmunity, inflammation, and cancer has drawn close attention [7][8][9][10]. m 6 A is the most common posttranscription modification of RNA [11].…”
Section: Introductionmentioning
confidence: 99%
“…YTHDF2, a N6-methyladenosine (m6A) "reader" protein, is a confirmed binder of c-Myc mRNA and is involved in increasing stability and expression of c-Myc in K562 cells, the same cells used in this study (Su et al 2018). The m6A modification can be added to nascent transcripts during maturation events (Ke et al 2017) and correlates with enhanced c-Myc mRNA translation (Hong 2018). RPL11 is involved in the regulation of c-Myc mRNA stability and promotes degradation by binding to the 3 ′ -UTR and recruiting the RNAinduced silencing complex (miR-24/RISC complex) to the c-Myc transcript in response to ribosomal stress (Challagundla et al 2011).…”
Section: Known C-myc Rbps Identified By Hypr-msmentioning
confidence: 94%
“…Moreover, m 6 A-dependent mRNA regulation has now been demonstrated to regulate the process of circadian rhythm, adipogenesis, spermatogenesis, embryonic stem cell self-renewal and differentiation (Fu et al, 2014). The aberrant regulation of m 6 A is related to a variety of cancers including acute myeloid leukemia, breast cancer, glioblastoma, lung cancer and liver cancer (Hong, 2018; Luo et al, 2018), which highlight the important regulatory roles of m 6 A.…”
Section: Introductionmentioning
confidence: 99%